Novel uniplanar pedicle screw systems applied to thoracolumbar fractures: a biomechanical study - Jiang, Yuheng; Cui, Xiang; Ji, Wei; Li, Jia; Shi, Yanli; Zhao, Jingxin; Wang, Junsong; Tang, Peifu; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
Objective. In this study, the advantages of the internal fixation configuration composed of uniplanar pedicle screws in the treatment of thoracolumbar fractures were verified by biomechanical experimental methods, which provided the basis for subsequent clinical experiments and clinical applications. Methods. A total of 24 fresh cadaveric spine specimens (T12-L2) were utilized to conduct biomechanical experiments. Two different internal fixation configurations, namely the 6-screw configuration and the 4-screw/2-NIS (new intermediate screws) configuration, were tested using fixed-axis pedicle screws (FAPS), uniplanar pedicle screws (UPPS), and polyaxial pedicle screws (PAPS) respectively. The spine specimens were uniformly loaded with 8NM pure force couples in the directions of anteflexion, extension, left bending, right bending, left rotation, and right rotation, and the range of motion (ROM) of the T12-L1 and L1-L2 segments of the spine was measured and recorded to access biomechanical stability. Results. No structural damage such as ligament rupture or fracture occurred during all experimental tests. In the 6-screw configuration, the ROM of the specimens in the UPPS group was significantly better than that of the PAPS group but weaker than those of the FAPS group (p<0.01). In the 4-screw/2-NIS configuration, the results were identical to the biomechanical test results for the 6-screw configuration (p<0.01). Conclusions. Biomechanical test results show that the internal fixation configuration with UPPS can maintain the stability of the spine well, and the results are better than that of PAPS. UPPS has both the biomechanical advantages of FAPS and the superiority of easy operation of PAPS. We believe it is an optional internal fixation device for minimally invasive treatment of thoracolumbar fractures.